Microbiological Investigation of Waste Water Discharge from Temple and Nkwelle Abattoir - V.G., Awari; J.P., Ofunnwa; N. C., Nwozor; O.C., Soludo; K.I., Imo; F.O., Nwajiobi; A.U., Chukwu; K.C., Agu; F.I., Ogujiofor; N.S., Awah; T.M., Agor (International Journal of Multidisciplinary Approach Research and Science, 2025)
The increasing volume of waste generation and inadequate disposal systems in Nigeria, particularly due to anthropogenic activities such as the indiscriminate location of slaughterhouses near residential areas, poses significant environmental and public health risks. This study investigated the microbiological quality of wastewater discharged from two slaughterhouses (Temple and Nkwelle) in Umunya, Oyi Local Government Area, Anambra State. Wastewater samples were collected using sterile containers and immediately transported to the microbiology laboratory for analysis. Bacterial isolation was conducted using Nutrient agar, Salmonella/Shigella agar, and MacConkey agar, while fungal isolation was performed using Potato Dextrose agar. The Total Heterotrophic Bacterial Counts (THBC) for Temple and Nkwelle slaughterhouses were 6.8 × 10⁵ CFU/mL and 5.2 × 10⁵ CFU/mL, respectively, while the Fungal Counts were 1.4 × 10⁴ CFU/mL and 1.2 × 10⁴ CFU/mL, respectively. Bacterial isolates included Escherichia coli, Bacillus spp., Citrobacter spp., Streptococcus spp., Proteus spp., Enterobacter faecalis, Klebsiella spp., Lactobacillus spp., and Staphylococcus aureus. Fungal isolates comprised Penicillium spp., Aspergillus spp., and Mucor spp. The findings indicate that slaughterhouse wastewater discharges contain high microbial loads of pathogenic bacteria and fungi, posing serious environmental contamination and public health risks, including potential waterborne diseases and ecological disruption. This study underscores the urgent need for sustainable and environmentally friendly waste management practices in slaughterhouse operations. Recommendations include implementing proper wastewater treatment systems, enforcing regulatory measures, and promoting public awareness to mitigate the adverse impacts on the environment and human health.